Sanctuary - Wharton, Edith, 1862-1937 (Pine Street Books, 2001)
Kate Orme is a young woman whose illusions of marital bliss are shattered when she comes face to face with the dark secret harbored by her fiance, the wealthy and deceptively ebullient Denis. Kate decides to go ahead and marry Denis, however, as a selfless gesture to protect any child he may conceive from inheriting their father's moral weakness. The couple does have a child, Dick, and in a marriage with a man that Kate has admittedly ceased to love, she transfers her original affections for Denis to their son. Denis dies suddenly and Kate is left to raise their young son. Knowing that Dick could have inherited the faults of his father, Kate anticipates a time when Dick's morality will be severely tested. That time comes years later when Dick, an eligible bachelor and aspiring professional, is faced with a dilemma that will affect the course of his life. With the precision, beauty, and sharp awareness of the cracks in upper-class New York society that made her one of the great writers of the twentieth century, Edith Wharton offers a subtle critique of the nature versus nurture debate that raged in the early 1900s. Sanctuary is a spare and moving investigation of the forces that impel human beings toward sin, self-doubt, and redemption.